Memórias e saberes de velhos e velhas: tessitura da oralidade em comunidades de terreiro - Azevedo, Ivan Elias de (2024)
Historically, the tradition of orality is used by African communities as the main means of transmitting knowledge between Masters and Apprentices. In Brazil, Afro-diasporic communities have been using this tradition as their main means of transmitting knowledge. Given this, this research proposes to analyze the ways in which older people learned and transmit knowledge through orality, and how younger people are absorbing and being prepared in the context of safeguarding these memories as heritage. The methodology used is qualitative in nature, using three tools as a data collection technique, namely the Focus Group, Conversation and Self-narrative. Thematic Analysis was used to analyze the data. It was possible to observe a concern among older people with the future of the tradition due to the way in which young people are dealing with the advancement of technology and the great flow of information that digital media provide for today's society, however, orality and experience are still They are the main means of transmitting knowledge used by Candomblé communities and continue, together with respect and reverence for ancestry, as philosophical bases. It is also considered that Candomblé is in a movement of constant change due to the process of cultural hybridization and the advancement of information technologies in its practices, however, despite the concern of the elderly with the continuity of Candomblé, young people are conscious and engaged in maintaining tradition, and perpetuating knowledge as a cultural and religious heritage of terreiro communities.